If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(4x+3)=10x+5-2x+1
We simplify the equation to the form, which is simple to understand
2(4x+3)=10x+5-2x+1
Reorder the terms in parentheses
+(+8x+6)=10x+5-2x+1
Remove unnecessary parentheses
+8x+6=+10x+5-2x+1
We move all terms containing x to the left and all other terms to the right.
+8x-10x+2x=+5+1-6
We simplify left and right side of the equation.
0x=0
0=0
This equation is an identity, so all real numbers are solutions.
| 5s-18=8x | | 30x+29x+2=180 | | 4(w+1)=-2(1-2w) | | Log(3x)+5=7.3 | | 7=313-9x | | 30=29x+2 | | 8(2x-1)2+3=-10(2x-1) | | -9(3)+3y=-27 | | 3x+25x-6=7(4x+1) | | f(2)=4.25x+5 | | 0.7p+4.6=5d | | -9(-9)+3y=-27 | | -6*2.2= | | 3(a+5)=9[a-(4-a)] | | -6k+3=-3(2k-1) | | (9x+5)+(26x)=180 | | 2y-36=36 | | 27-(2c+3)=2(c+7)+c | | 4-(6+h)= | | X^2-17=13-x^2 | | 2n+32(2)=126 | | 9(b-4)-8=5d | | (22x+2)=(21x+6) | | 3(3x-15)=6(x-15) | | -6(a+1)+a= | | y=(0.0036*8)7 | | 12*b=480 | | -3(-2+4p)+3=-51 | | y=-.6(12.5)+3 | | 0.12(y-2)+0.10y=0.02y-2.1 | | 1.02-0.5=0.1m+0.7 | | y-9=1*2(x-7) |